Sedimentological responses to the Hunter–Bowen Orogeny (eastern Australia): evidence from the northern Gympie Terrane. Issue 1 (2nd January 2020) - Rosenbaum, G.; Slade, A.; Hoy, D.
Abstract: The volcano-sedimentary succession of the Gympie Terrane is an important record of the eastern Gondwana subduction boundary during the Permian and Triassic. Previous work in this region has focused mainly on the geology of the Gympie Goldfields in the southern part of the Gympie Terrane, whereas the northern part has remained relatively understudied. Here we present sedimentological and structural observations from the northern Gympie Terrane, complemented by new U–Pb detrital zircon data from key stratigraphic units. The stratigraphic succession comprises deep-marine lower Permian mudstones and volcaniclastic rocks derived from a distal volcanic source, overlain by shallow-marine middle–upper Permian carbonate and siliciclastic rocks. The Lower Triassic rocks are dominated by terrestrial alluvial fan deposits, which are overlain by Middle Triassic shallow-marine facies rocks. Our new detrital zircon data show that the cessation of deep-marine sedimentation had occurred prior to ca 263 Ma, possibly in response to the onset of the Hunter–Bowen Orogeny. Deformation and uplift associated with the Hunter–Bowen Orogeny led to an increasing proportion of recycled detritus in the sediments, as indicated by the detrital zircon data. The second phase of Hunter–Bowen Orogeny, at ca 250 Ma, likely led to the transition to a terrestrial depositional setting, and the increased input of recycled continental material into the sedimentary basin. The uppermost units in the Gympie Terrane are Middle Triassic marine successions, which were deposited in a period of tectonic relaxation prior to the last phase of the Hunter–Bowen Orogeny at 235–230 Ma. Highlights: The geology of the Gympie Terrane provides an insight into the evolution of the eastern Gondwanan subduction boundary during the Permian and Triassic. A broadly correlative stratigraphy is recognised in the northern and southern parts of the Gympie Terrane. The cessation of deep-water deposition in the Gympie Terrane coincides with the first phase of Hunter–Bowen Orogeny. Changes in detrital zircon provenance in the Gympie Terrane correspond to the timing of tectonic switches along the convergent plate boundary of eastern Gondwana.